The study of religion under the impact of fascism - Junginger, Horst. (Numen Book Series, 2008)
The study of religion under the spell of fascism has not received due attention. One reason for the noticeable lack of interest was the political involvement of many historians of religions. Among those who had good reason to leave the era of fascism untouched, we find prominent figures in the field. Another obstacle to examining the past impartially has been the connection with religious and other worldviews which render historical accounts in the study of religion an intricate matter. The articles in this volume provide evidence of the great complexity of the problems involved. Laying the groundwork in many cases, they shed new light on a dark and poorly-lit era of the academic study of religion in Europe.